ATP-Dependent Chromatin Remodeling During Cortical Neurogenesis - Sokpor, Godwin; Castro-Hernandez, Ricardo; Rosenbusch, Joachim; Staiger, Jochen F.; Tuoc, Tran (Frontiers in Neuroscience, 2018)
The generation of individual neurons (neurogenesis) during cortical development occurs in discrete steps that are subtly regulated and orchestrated to ensure normal histogenesis and function of the cortex. Notably, various gene expression programs are known to critically drive many facets of neurogenesis with a high level of specificity during brain development. Typically, precise regulation of gene expression patterns ensures that key events like proliferation and differentiation of neural progenitors, specification of neuronal subtypes, as well as migration and maturation of neurons in the developing cortex occur properly. ATP-dependent chromatin remodeling complexes regulate gene expression through utilization of energy from ATP hydrolysis to reorganize chromatin structure. These chromatin remodeling complexes are characteristically multimeric, with some capable of adopting functionally distinct conformations via subunit reconstitution to perform specific roles in major aspects of cortical neurogenesis. In this review, we highlight the functions of such chromatin remodelers during cortical development. We also bring together various proposed mechanisms by which ATP-dependent chromatin remodelers function individually or in concert, to specifically modulate vital steps in cortical neurogenesis.